EduGuard RetainX: An advanced analytical dashboard for predicting and improving student retention in tertiary education - Nornina J. Dia; Joseph C. Sieras; Suhaina A. Khalid; Amer Hussien T. Macatotong; Jeffrey M. Mondejar; Elizabeth R. Genotiva; Reymark D. Delena (SoftwareX)
Students’ attrition is a critical challenge in higher education, and the EduGuard RetainX software represents a transformative solution. To accurately identify at-risk students, this innovative platform harnesses advanced predictive analytics with knowledge of the personal and institutional costs of student dropout. Using the software, educators can provide students with tailored, student-centric support early on. In addition, the software fosters a collaborative, data-driven culture that allows a wide range of stakeholders to contribute to student success initiatives. The platform has demonstrated significant positive effects and real advantages, as shown by thorough evaluations of its usability using Dowding and Merrill's usability checklist, where it achieved an 89 % usability score. Further, by enabling a shift towards evidence-based practices and a relentless focus on supporting academic achievement and student persistence, the software is poised to completely reshape the higher education landscape.